Rates and impact of vascular complications in mechanical circulatory support. Issue 5 (9th March 2022) - Lemor, Alejandro; Dabbagh, Mohammed F.; Cohen, David; Villablanca, Pedro; Tehrani, Behnam; Alaswad, Khaldoon; Alqarqaz, Mohammad; Lasorda, David; Kaki, Amir; Genereux, Philippe; O'Neill, William; Basir, Mir B.
Abstract: Background: Mechanical circulatory support (MCS) devices are increasingly used for hemodynamic support in cardiogenic shock or high‐risk percutaneous coronary interventions. Vascular complications remain a major source of morbidity and mortality despite technological advances with percutaneous techniques. Little is known about the rates and predictors of vascular complications with large‐bore access MCS in the contemporary era. Methods: The study cohort was derived from National Inpatient Sample using data from 2015 to 2019 for cardiac hospitalizations with the use of: intra‐aortic balloon pump (IABP) Impella, and/or extracorporeal membrane oxygenation (ECMO). The rates of vascular complications and in‐hospital outcomes were analyzed using multivariable logistic regression. Results: Of 221, 700 hospitalizations with MCS use, the majority had only IABP (68%). The rates of vascular complications were greatest with ECMO (15.8%) when compared with IABP (3.0%) and Impella (5.6%). Among patients with vascular complications, in‐hospital mortality was higher with ECMO (56.3%) when compared with IABP (26.2%) and Impella (33.8%). Peripheral arterial disease (PAD) was the strongest predictor of vascular complications, with 10 times higher odds when present (adjusted odds ratio [aOR] 10.96, p  < 0.001). In risk‐adjusted models, when compared with IABP, the use of Impella (aOR: 1.73, p  < 0.001), ECMO (aOR: 5.35, p  < 0.001), or a combination of MCS devices (aOR: 3.47, p  < 0.001) was associated with higher odds of vascular complications. Conclusions: In contemporary practice, the use of MCS is associated with significant vascular complications and in‐hospital mortality. Predictors of vascular complications include larger arteriotomy size, female gender, and peripheral arterial disease. Vascular access management remains essential to prevent major complications.